Age–Period–Cohort Analysis of Long Trend of Mortality for Stroke and Subtypes Attributed to High SBP in Chinese Adults - Ma, Yudiyang; Cao, Jinhong; Mubarik, Sumaira; Bai, Jianjun; Yang, Donghui; Zhao, Yudi; Hu, Qian; Yu, Chuanhua (Frontiers in Neurology, 2022)
This study aims to analyze the long-term trends of mortality for stroke and its subtypes attributed to high SBP stratified by age and gender among Chinese adults. The data were retrieved from the Global burden of disease (GBD) study database. This study analyzed the mortality of stroke and subtypes attributed to high systolic blood pressure over the past 30 years via the age-period-cohort model. The age-standardized mortality rates of stroke mortality attributed to high systolic blood keep declining but still above the global level. The overall net drifts per year are -3.19% and -5.45% for stroke in Chinese males and females. The local drifts values of stroke and subtypes present downward trends in males while oscillated trends appear in females; all local drifts values of females are lower than their counterparts of males. Age effects increase with age for both genders, with the increasements for females fall behind males. Whereas the period and cohort effects in a similar decline trend, with the reductions for females are more significant than males (significantly with P<0.05 for all). There exist variations among all categories of stroke mortality attributed to high systolic blood pressure. Intracerebral hemorrhage overtook ischemic stroke as the most lethal subtype of stroke even if mortality risk for subarachnoid hemorrhage is under control. Stroke and its subtypes mortality attributed to high systolic blood pressure in Chinese adults have decreased from 1990 to 2019. However, intracerebral hemorrhage and ischemic stroke mortality attributed to high systolic blood pressure is still the first and second lethal subtype of stroke. It is necessary to educate the citizens with the correct knowledge and techniques to control blood pressure.